Analysis of the Behavior of Variable and Fixed Costs as a Tool for Operational CPV-Analysis - Akbarovna, Sultonova Shahlo; R. , Nazarova R. (Research Parks Publishers, 2023)
The article considers the importance of the operational analysis in the division of costs into fixed and variable, since the presence of such groups of costs provides an objective assessment of the effectiveness of enterprises. This necessitates the disclosure of the essence of variable and fixed costs, the study of their ratio, as well as their impact on the cost of production.